Purification of a soluble isoform of guanylyl cyclase-activating-factor synthase. - Schmidt, H H (1991)
The soluble form of guanylyl cyclase-activating-factor (GAF) synthase from rat cerebellum was purified to homogeneity by sequential affinity chromatographic steps on adenosine 2',5'-bisphosphate (2',5'-ADP)-Sepharose and calmodulin-agarose. Enzyme activity during purification was bioassayed by the L-arginine-, NADPH-, and Ca2+/calmodulin-dependent formation of a plasma membrane-permeable nitric oxide-like factor that stimulated soluble guanylyl cyclase in RFL-6 cells. With calmodulin and NADPH as cofactors, purified soluble GAF synthase induced an increase of 1.05 mumol of cGMP per 10(6) RFL-6 cells per 3 min per mg of protein. The coproduct of this signal-transduction pathway appeared to be L-citrulline. GAF synthase catalyzed the conversion of 107 nmol of L-arginine into L-citrulline per min per mg of protein. Based on these assays, this represents a purification of GAF synthase of approximately 10,076- and 8925-fold with recoveries of 16% and 19%, respectively. Rechromatography of the purified enzyme on Mono P (isoelectric point = 6.1 +/- 0.3), Mono Q, and Superose 12 or 6 resulted in no further purification or increase in specific activity. A Stokes radius of 7.9 +/- 0.3 nm and a sedimentation coefficient s20,w of 7.8 +/- 0.2 S were used to calculate a molecular mass of about 279 +/- 25 kDa for the native enzyme. SDS/PAGE revealed a single protein band with a molecular mass of about 155 +/- 3 kDa. These data suggest that soluble GAF synthase purified from rat cerebellum is a homodimer of 155-kDa subunits and that enzyme activity is dependent upon the presence of calmodulin.